Vigilantisme dan Ketimpangan Penegakan Hukum : Studi Kasus Penghakiman Massa terhadap Pelaku Pencurian Motor - Intan Sahwa; Hana Salsabila; Jubilla Hafitri; Fadiya Annisa Salsabila; David Nugraha Saputra (Pusat Riset dan Inovasi Nasional, 2025)
This study discusses the phenomenon of vigilantism or vigilante action that occurred in the case of mass judgment against motorcycle theft perpetrators in Perum Kota Batara, Tangerang. This study uses a qualitative approach with a literature study method to analyze the relationship between inequality in law enforcement, public distrust of legal institutions, and the social background of collective violence. The results of the study indicate that the emergence of vigilante action does not occur in a vacuum, but is triggered by public frustration with the legal system which is considered slow and unfair, especially towards the common people. In the context of urban society with high social inequality, people tend to create their own form of justice through direct violence. This phenomenon is a signal that the state has not been optimally present in ensuring a sense of security and justice for all its citizens. Therefore, responsive and educative legal reform is needed so that justice is not just a slogan, but is truly felt by society as a whole.